ChemInform Abstract: Three‐Component Azidation of Styrene‐Type Double Bonds: Light‐Switchable Behavior of a Copper Photoredox Catalyst. Issue 5 (January 2016) - Fumagalli, Gabriele; Rabet, Pauline T. G.; Boyd, Scott; Greaney, Michael F.
Abstract: The copper‐catalyzed reaction of indene and styrene with Zhdankin reagent in MeOH in the presence of light gives rise to methoxy azides (III) and (VII), whilst the reaction in the dark leads to diazides (IV)/(V) and (VIII).